Mechanical Properties and Microstructure of High Ductility Solidified Silt - ZHANG Chao-jie, HONG Yu-ze, CHENG Ze-hai, JIN Liu-jun, LING Hao-jun (长江科学院院报)
[Objectives] The silt foundations of Qiantang River seawalls exhibit weak impermeability and are prone to water erosion and loss. During periods of strong tidal bores and floods, soil flowing and piping are likely to occur, leading to seawall defects and seepage deformation or cavities in the seawall foundation. To address these issues, solidification and improvement measures are necessary. [Methods] This paper focuses on the different improvement properties of curing agents and employs a controlled-variable method to conduct silt solidification ratio experiments. The improvement of solidified silt were analyzed through unconfined compressive strength tests and permeability tests. XRD was employed for changes in mineral composition and chemical products before and after silt solidification, and SEM tests were conducted to observe the microstructural changes caused by the addition of chemical reagents. ImageJ software with machine learning capabilities was utilized to process SEM images to quantify the correlation between mechanical properties and microstructural characteristics. [Results] The optimal solidifying agent composition consisted of 4% cement, 1% fly ash, 1% lignin, 1% HV, and 1% CMC. This formulation resulted in a 28-fold increase in failure strain and a lower permeability coefficient than that of the original silt. In a permeable environment, the permeability coefficient of the solidified silt gradually decreased over time until it stabilized. SEM revealed hydrated calcium silicate (C-S-H) and ettringite (AFt) from cement hydration in the solidified silt, as well as glassy silica-alumina in a spherical fly ash morphology filling the pores. Quantitative analysis using Image J software indicated that the C4H1-solidified silt exhibited the greatest increase in failure strain and porosity, achieving the best ductility effect. Curve-fitting uncover that the correlation between pore count and strength in the modified solidified silt was not significant, while failure strain showed a positive correlation with porosity. [Conclusion] By transcending the limitations of traditional research, which often focuses on a single property (strength or impermeability), this study achieves synergistic improvement of both high ductility and impermeability, providing a more comprehensive solution for engineering applications. Additionally, the use of ImageJ software for quantitative analysis of pore structure has revealed a positive correlation between porosity and failure strain, offering a microscopic explanation for macroscopic properties.